Lepidopteran caterpillar fauna on lactiferous host plants in the central Brazilian cerrado - DINIZ, I. R. (1999)
Nine lactiferous plants of five families were examined for caterpillars in a 4 ha cerrado sensu stricto (savanna-like vegetation) area of the University of Brasília Experimental Farm (DF, Brazil), from August 1995 to May 1997. In 5,540 censuses, less than 5% of the plants hosted caterpillars. All the caterpillars found, a total of 55 species in 15 families were reared under laboratory conditions. Pyralidae, Geometridae, Elachistidae, Megalopygidae, and Limacodidae were the richest caterpillar families recorded. Of the 55 species, more than 40% were polyphagous, feeding on different host plant families, while 21 were considered rare species with less than four records during the study period. The species' rareness did not permit any analysis of diet breadth. The presence of latex in the host plants seems to affect both the proportion of host plants with caterpillars (abundance) and the caterpillar species richness. The habit of eating plants that characteristically produce latex occurs in several distantly-related lepidopteran families. The results support the argument that specific behaviors to circumvent plant latex defense may have arisen independently many times in the Lepidoptera.